Commodity market trends and instabilities : policy options for developing countries. - MAIZELS, Alfred (1994)
Considers the adverse shift in the international markets for the commodity exports of developing countries, which has resulted in huge real income losses for these countries. Concludes that the deterioration in real export earnings was almost certainly a major cause of the huge increase in the external debt of these countries since the early 1980's. Recommends that a new approach to evolving an effective and coherent international policy aimed at strengthening the economies of commodity-dependent developing countries should consider the immediate issues, viz. depressed prices and excessive price instability, together with the main longer-term issues, since these are generally interdependent.